2016
DOI: 10.1111/maps.12661
|View full text |Cite
|
Sign up to set email alerts
|

The Agoudal (High Atlas Mountains, Morocco) shatter cone conundrum: A recent meteorite fall onto the remnant of an impact site

Abstract: Associations between impact structures and meteorite occurrences are rare and restricted to very young structures. Meteorite fragments are often disrupted in the atmosphere, and in most cases, meteorite falls that have been decelerated by atmospheric drag do not form a crater. Furthermore, meteorites are rapidly weathered. In this context, the finding of shatter cones in Jurassic marly limestone in the same location as a recent (105 ± 40 ka) iron meteorite fall near the village of Agoudal (High Atlas Mountains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 58 publications
3
39
0
Order By: Relevance
“…Vertical to overturned N150–N160 trending strata, not observed elsewhere in the surrounding area, were reported by Chennaoui Aoudjehane et al. (). The breccias within the area of SC occurrence were considered to be impact breccias, based on the presence of cryptocrystalline inclusions, and were interpreted as possible relics of weathered impact melt rocks (Lorenz et al.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Vertical to overturned N150–N160 trending strata, not observed elsewhere in the surrounding area, were reported by Chennaoui Aoudjehane et al. (). The breccias within the area of SC occurrence were considered to be impact breccias, based on the presence of cryptocrystalline inclusions, and were interpreted as possible relics of weathered impact melt rocks (Lorenz et al.…”
Section: Introductionsupporting
confidence: 73%
“…Agoudal is the only known impact structure in Morocco (Chennaoui Aoudjehane et al. ). It was confirmed by the observation of well‐preserved shatter cones (SCs) in a mid‐Jurassic marly limestone formation (Sadilenko et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, based on the terrestrial age of the Agoudal find, Chennaoui Aoudjehane et al. () concluded that the meteorite fall on the Earth postdates the formation of shatter cones and it is a mere coincidence that the meteorite fell on a previously formed impact structure. In Meteorite Database (Meteoritical Bulletin 102, 2013), Agoudal has been classified as IIAB based on its bulk composition and structural similarity with Ainsworth (Buchwald ).…”
Section: Introductionmentioning
confidence: 99%